EVALUATION OF ANTIDIABETICS USAGE AMONG PATIENTS WITH ULCER DIABETIC - Recta Olivia Umboro; Djoko Wahyono; I Dewa Putu Pramantara (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetic ulcers and gangrene are the most frequent cases of diabetes that are hospitalized. Several studies in Indonesia showed that 17-23% of the mortality rate was due to ulcers or gangrene and 15-30% was due to amputation. Blood glucose control is an integral factor which affects the successful management of diabetic ulcers. Blood glucose control can be done by the management of pharmacologic therapy, either in the form of oral antidiabetics therapy, insulin, or a combination of both. This was a nonexperimental research with descriptive evaluative design using a retrospective data through the medical records of patients with a T2DM diabetic ulcers diagnosis. This research was conducted in PKU Muhammadiyah Yogyakarta hospital period January 2010-December 2011. Data were analyzed with descriptive analysis and chi-square evaluation on the correlation between the type of therapy and blood glucose levels, and the correlation between blood glucose levels and the clinical outcome of patients T2DM diabetic ulcers. The results showed that the usage pattern of antidiabetics in patients with T2DM in PKU Muhammadiyah Yogyakarta hospital were insulin (46.7%), oral hypoglycemic drugs (OHD) 18.1%, the combination therapy of OHD-OHD (20.5%), the combination therapy of insulin-OHO (13.9%), and the combination therapy of insulin-insulin (0.8%). The type of insulin which is mostly used was rapid acting insulin (67.9%), biguanid was mostly used for OHD (68.2%). As for the combination therapy, OHD-OHD that was mostly used was biguanid-sulfonylurea (94%), the combination of insulin and OHD that was majority used was insulin-biguanid, and the combination of insulin-insulin that was mostly used was long acting-rapid acting insulin (100%). The results of chi-square analysis showed that there were significant correlation (p = 0.016) between the type of therapy and blood glucose levels, and between blood glucose levels and diabetic ulcer clinical outcome (p = 0, 00).Keywords: diabetic ulcers, antidiabetics, blood glucose levels, clinical outcomes.